Penciptaan Lingkungan Edukatif dalam Pembentukan Karakter: Studi terhadap Aplikasi Pemikiran Ibnu Jama’ah - Hery Noer Aly (TSAQAFAH, 2012)
This study is a rediscovery enterprise on educational thought of Ibn Jama’ah in his famous book, al-Tadhkirah. It is basically the book on  learning and teaching. But, much more  than a book on  technic and strategy ,  it  is  full of  moral message which conducts whole process of  learning and  teaching,  and  in  turn  creates an  educating environment. The significance of this study due to moral decadence among the nation. Corruption, for instance, is not only available among the leaders and bureaucrates, but also among the peoples. Delinquency  is not only the habit of  young generation, but now suffered by parents who can not give a good sample. That moral decadence is not deal with  the poverty of moral conduct; there  are  treasury  and haritage of  it, either from religous or traditional resource. But that old values available in many documents are not internalized yet, in additon to the fast-coming of foreign culture which is not in accord with Indonesian culture. Here we see that the issue is not the content of value education, but the strategy developed  in the process. So that, al-Tadhkirah will be studied with content analysis approach to find out the possibility of application of his thought in moral education. The study  finally discovered that the  thought of  Ibn  Jama’ah  is very possible  to be applied. The only precondition  is the commitment of all stakeholders to create educating environtment based on regulation formulated by themselves.